REGIONAL ASSESSMENT OF HUMAN CAPITAL IN THE REPUBLIC OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
This article discusses approaches to the assessment of human capital. Drawing on international research experience, a standard international assessment methodology, and regional statistical data, a methodology for assessing human capital of the Republic of Uzbekistan at the regional level is proposed. Based on the author's methodology, the human capital of the regions of the Republic of Uzbekistan is evaluated.